2015
DOI: 10.1007/s10529-015-1877-2
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 20(S)-protopanaxatriol by Mucor racemosus and the anti-cancer activities of some products

Abstract: Biotransformation by M. racemosus AS 3.205 was an effective approach to produce new derivatives of 20(S)-protopanaxatriol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that M. racemosus may be employed to biotransform some steroid compounds, such as progesterone [15], methyltestosterone [16] and 20(s)-protopanaxatriol [17] to intermediates with anti-cancer activities. Likewise, the fungus grown on synthetic and organic substrates may be used for the production of various enzymes such as invertase, alkaline phosphatase, protease and lipase, which are of biotechnological and bioremediation interest [18].…”
mentioning
confidence: 99%
“…Recent studies have shown that M. racemosus may be employed to biotransform some steroid compounds, such as progesterone [15], methyltestosterone [16] and 20(s)-protopanaxatriol [17] to intermediates with anti-cancer activities. Likewise, the fungus grown on synthetic and organic substrates may be used for the production of various enzymes such as invertase, alkaline phosphatase, protease and lipase, which are of biotechnological and bioremediation interest [18].…”
mentioning
confidence: 99%